Fiscal spillovers in the Euro area - Guglielmo Maria Caporale; Alessandro Girardi (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper analyses the dynamic effects of fiscal imbalances in a given EMU member state on the borrowing costs of other countries in the euro area. The estimation of a multivariate, multi-country time series model (specifically a Global VAR, or GVAR) using quarterly data for the EMU period suggests that euro-denominated government yields are strongly linked with each other. However, financial markets seem to be able to discriminate among different issuers. Consequently, fiscal imbalances in Italy and in other peripheral countries should be closely monitored by their EMU partners and the European institutions.
Keywords: C32; E62; F42; H63; 330; global VAR methodology; fiscal spillovers; euro area; public debt; Öffentliche Schulden; Spillover-Effekt; Rendite; Öffentliche Anleihe; Kapitalkosten; Eurozone